An observational investigation of the faical microbiota and metabonome of gastrostomy fed children, on blended and formula diets. (31st December 2022) - Marchesi, Julian R.; Allen, Sophie; Scott, Emma; Jenkins, Huw; Sadlier, Claire; Thomas, Sian
ABSTRACT: Gastrostomy fed children traditionally have a Formulae diet (FD), which fulfills nutritional requirements; however, many families are adopting Blended diets (BD), which are what the whole family would eat. We undertook an observational investigation of the colonic microbiota and metabonome in a small group of gastrostomy fed children, who were either on an FD or BD, and compared, where possible to their siblings (17 FD, 28 BD, 19 HS). There was no increase in complications in tube blockage or infection rates, but a significant improvement in the prevalence of bowel problems, a reduction in medication and an increase in quality of life. Metataxonomic analysis showed that the FD group was significantly different to the Sibling group, and that families did not cluster together. Whole sample metabonomics showed no differences between groups; however, univariate analysis of biologically important metabolites did differ. Changing to a BD resulted in no increase in complications or risks, but improved the overall quality of life for the children and families.